Innovative Teaching as the Foundation for Students’ Academic Success - Khoruzha, Liudmyla (Educological discourse, 2025)
The article explores the essence of innovation in the professional activities of educators as a tool for improving education quality and the success of its recipients. It emphasizes that innovation in education is systemic and multifaceted, capable of fostering development on individual, institutional, and societal levels. A key indicator of this impact is the academic success of students. The study concludes that the innovativeness of an educator’s activities serves not only as a context but also as a resource for the personal and professional growth of students, ensuring their academic success. In this research, academic success is viewed as a holistic, multi-component concept, not limited to high academic performance alone. A graphical representation of the relationship between innovativeness and the groups of factors influencing students’ academic success is provided.